Instagram Optimization as A Marketing Tool and Strengthening Relationships with Customers - Putri, Salsabila Rihardi Adali; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to develop a business strategy for PT Galari Promosindo Prima to strengthen its strategic position and enhance its competitiveness in Indonesia's Event Organizer industry. The research is based on an analysis of the company's internal and external environmental conditions, alongside strategic considerations essential for business development planning. A descriptive qualitative approach was employed, utilizing interviews, observations, and documentation for data collection. The analytical tools used include Social Media Optimization (SMO) to evaluate the company's internal and external environment, SWOT analysis and its matrix to generate potential strategic alternatives, and stakeholder alignment to finalize the recommended strategy. The findings suggest that the most suitable strategy for PT Galari Promosindo Prima, given its current conditions, is implementing SMO. This strategy emphasizes improving social media presence through a well-planned content production timeline, enhancing visual appeal on Instagram, monitoring social media performance, and leveraging Instagram analytics tools to optimize digital marketing efforts.